Vocabulary development in a CLIL context: A comparison between French and English L2 - Baten, Kristof; Van Hiel, Silke; De Cuypere, Ludovic (Studies in Second Language Learning and Teaching, 2020)
Content and language integrated learning (CLIL) has expanded in Europe, favored by the large body of research, often showing positive effects of CLIL on L2 development. However, critical voices have recently questioned whether these positive findings apply to any language, given that most research focuses on English. Taking into account this concern, the present study investigated the (productive and receptive) vocabulary development in L2 English and L2 French of the same group of learners within a CLIL context. The aim was not to evaluate the benefits of CLIL over non-CLIL, but, instead, to examine whether vocabulary gains in CLIL learning are language-dependent. More specifically, this study included 75 Flemish eight-grade pupils who had CLIL lessons in both English and French. The results show that although the pupils have a larger English vocabulary, the level of improvement (from pretest to posttest) is not different across the languages. The findings indicate that within CLIL vocabulary knowledge also develops in languages other than English.